Analisis Diversifikasi, Merger, dan Akuisisi - Risma Warti; Dea Dara Audina; Adelia Azizi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2022)
Diversification analysis was developed with various objectives including increasing growth when the existing market/product has reached a maturity stage, maintaining stability by spreading the risk of fluctuations in profit, increasing credibility in the capital market, to avoid dependence on a single good or product circulating in the market, fulfill the wishes of unsatisfied consumers, increase the attractiveness or interest of consumers, increase sales turnover, increase profits by using the same ingredients, and prevent consumer boredom. Keywords: Diversification, Merger, and Acquisition.